Evaluation Of Combustion Characteristic On 2d Cylindrical Combustion Chamber For Different Operating Conditions And Using Alternative Fuels - Sim, Sing Mei (Universiti Sains Malaysia, 2019)
The study conducted is on simulation of a two-dimensional (2D) case of a cylindrical combustion chamber. The objective of the study is to evaluate the effects of different operating conditions on the combustion characteristics of 2D cylindrical combustion chamber. The software used to perform this study is ANSYS Fluent. Research was done by using different operating conditions including fuel temperature, droplet sizes, fuel injectors and type of fuel. The fuels used were Jet-A which is the conventional fuel for aircrafts, and alternative fuels including Jatropha Bio-synthetic Paraffinic Kerosene (JSPK), Camelina Bio-synthetic Paraffinic Kerosene (CSPK), mixture of 50% JSPK with 50% Jet-A (50JSPK/50Jet-A) and mixture of 50% CSPK with Jet-A (50CSPK/50Jet-A). Droplets size were varied to study the effect of droplet-size distribution (DSD) on spray combustion processes. Results had proven that smaller droplet size will lead to high combustion rate and thus better efficiency. Effects of fuel temperature at 300 K, 400 K and 500 K were analysed. Higher fuel temperature produced better evaporation in the chamber. Besides, every fuel listed were simulated at different spray half cone angles, which are 30°, 40° and 50°. From the simulation, it is shown that higher spray half cone angle produced shortest penetration length and took shortest time for droplets to reduce in its diameter. 50JSPK/50Jet-A and 50CSPK/50Jet-A had the shortest time to evaporate where it indicated that both fuel mixtures have higher evaporation rate due to lower boiling point and density.